E-Learning Pattern Between Effectiveness and Obstacles as Viewed by Secondary School Students During the COVID-19 Pandemic in Jordan - Al-Mawadeh, Nofah Sameh; Alsnayan, Mutaz Nayef; ALkhtaybeh, Majid Mohammad (Journal of Educational and Psychological Sciences, 2023)
The aim of this study is to evaluate E-learning pattern between effectiveness and obstacles as viewed by the secondary stage students during the COVID-19 pandemic in Jordan. The study population consisted of 326 eleventh-grade students from private schools in Madaba, Jordan. In addition, a sample of 142 eleventh-grade students was purposefully selected from Al-Rashad Schools in Madaba during the second semester of 2020/2021. The study used the descriptive methodology approach represented by a questionnaire developed to achieve the study's objectives. The study concluded that the difficulties and barriers of e-learning were generally moderate. Similarly, the usefulness of e-learning activities and the effectiveness of e-learning activities were at a moderate level. The study also concluded that there were no statistically significant differences in the level of evaluation of e-learning activities as viewed by the secondary stage students during the COVID-19 pandemic in Jordan.
Keywords: effectiveness; obstacles; e-learning; Covid-19 pandemic